(untitled) (Baghdad Science Journal, 2006)
Histologic changes were studied and physiological dosage crude alcoholic extract of seeds of the fenugreek plant for male mice eggs in different concentrations after oral to study testicular tissue and culverts where reason Abstract significant decrease